2022
DOI: 10.3389/fnut.2022.913106
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic-Assisted Dual-Alkali Pretreatment and Enzymatic Hydrolysis of Sugarcane Bagasse Followed by Candida tropicalis Fermentation to Produce Xylitol

Abstract: In this work, the investigation mainly focused on ultrasonic-assisted dual-alkali pretreatment and enzymatic hydrolysis of sugarcane bagasse followed by Candida tropicalis fermentation to produce xylitol. The results showed that the combination of NaOH and ammonia water had the best effect by comparing the effects of the four single-alkali (NaOH, KOH, ammonia water, Ca(OH)2) and their mixed double-alkali pretreatments on xylose content. Then, the optimal conditions for ultrasonic-assisted pretreatment and enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
(35 reference statements)
1
0
0
Order By: Relevance
“…Each sample had different morphological characteristics. It was found that bagasse were long strips of fibers and the structure was relatively flat and complete, which is consistent with the previous study ( 27 ). After AHP treatment, striated cracks were formed on the BIDF surface, which could be due to lignin degradation.…”
Section: Resultssupporting
confidence: 92%
“…Each sample had different morphological characteristics. It was found that bagasse were long strips of fibers and the structure was relatively flat and complete, which is consistent with the previous study ( 27 ). After AHP treatment, striated cracks were formed on the BIDF surface, which could be due to lignin degradation.…”
Section: Resultssupporting
confidence: 92%
“…Ultrasound has been widely used as a green and efficient physical treatment technique to assist enzyme hydrolysis (Gai et al, 2022;Hong et al, 2022). The cavitation and shearing effects of ultrasound have been shown to introduce changes in protein structure and molecular weight (Uluko et al, 2014), influencing the nature of the enzymatic products and enhancing the biological activity of the hydrolyzed peptides.…”
Section: Introductionmentioning
confidence: 99%